FACTORS INFLUENCING EFL STUDENTS’ UTILISATION OF TEACHER WRITTEN FEEDBACK - Omer Hassan Ali Mahfoodh (TEFLIN Journal, 2022)
This qualitative case study investigated factors affecting EFL university students’ use of teacher written feedback. Ten Yemeni EFL university students participated in this study. Data included students’ written essays, teacher written feedback, and semi-structured interviews. Students’ use of teacher written feedback was analysed using an adapted rating scheme. Thematic analysis was used for analysing the interviews. The results revealed that the major factors affecting students’ use of teacher written feedback are feedback-related factors (teachers’ use of correction symbols, legibility of written feedback, explicitness of written feedback, and wording of written feedback) and student-related factors (students’ emotional responses towards teacher written feedback and students’ previous literacy experience). Understanding the impact of these factors on students’ utilisation of teacher written feedback may help teachers to provide constructive and effective written feedback to their students. Training EFL students on how to utilise teacher written feedback successfully is important for improving the practice of teacher written feedback.